1996
DOI: 10.1210/jc.81.4.1460
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of estrone, estradiol, and estrone sulfate and evaluation of sulfatase and aromatase activities in pre- and postmenopausal breast cancer patients

Abstract: This report concerns the evaluation of various estrogens, estrone (El), estradiol (E2), and estrone sulfate (E1S), as well as E1S-sulfatase and aromatase activities in pre- and postmenopausal women with breast cancer. The levels (in picomoles per g; mean +/- SEM) of the various estrogens in the breast tissue from premenopausal patients (n = 11) are: El, 1.4 +/- 0.5; E2, 1.2 +/- 0.6; and E1S, 1.2 +/- 0.3. In postmenopausal patients (n = 23), the values are, respectively, 1.0 +/- 0.4, 1.4 +/- 0.7, and 3.3 +/- 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
163
2
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(185 citation statements)
references
References 0 publications
15
163
2
5
Order By: Relevance
“…Sulfatase mRNA levels were 10 2 -fold higher than aromatase mRNA in the present study and sulfatase activity has also been reported to be 400-to 500-fold higher than aromatase activity. 24,25 These results indicate that the sulfatase pathway is more important than aromatase pathway in the production of E1 in most breast tumors. However, Reed et al 26 demonstrated the presence of postmenopausal breast cancers in which the aromatase pathway can be more important than the sulfatase pathway by 3 H-androstendione and 14 Cestrone uptake study in patients.…”
Section: Discussionmentioning
confidence: 87%
“…Sulfatase mRNA levels were 10 2 -fold higher than aromatase mRNA in the present study and sulfatase activity has also been reported to be 400-to 500-fold higher than aromatase activity. 24,25 These results indicate that the sulfatase pathway is more important than aromatase pathway in the production of E1 in most breast tumors. However, Reed et al 26 demonstrated the presence of postmenopausal breast cancers in which the aromatase pathway can be more important than the sulfatase pathway by 3 H-androstendione and 14 Cestrone uptake study in patients.…”
Section: Discussionmentioning
confidence: 87%
“…However, another approach to this type of therapy has been to regulate ER responses by modulating the availability of endogenous ER ligand within tumour tissue. Local synthesis of oestrogens as a result of endogeneous aromatase, 17β-HSD and oestrone sulphatase activity has been demonstrated in endometrial (Maentausta et al, 1992), prostate (Elo et al, 1996) and breast tumours (Pasqualini et al, 1996). As a consequence, novel anti-cancer therapies have been aimed at controlling the local build-up of oestrogens in tumours by inhibiting the activity of specific steroidogenic enzymes, particularly aromatase and oestrone sulphatase (Brodie et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated for 1 day and thereafter treated with or without 10 À8 M oestradiol (17b-oestradiol; Apoteket, Umeå, Sweden), 10 À6 M tamoxifen (Sigma, St Louis, MO, USA) or a combination of oestradiol and tamoxifen. The dose of oestradiol may be considered physiological, taking into consideration the local production and accumulation of oestradiol in human breast tumours in vivo (van Landeghem et al, 1985;Vermeulen et al, 1986;Pasqualini et al, 1996). The concentration of tamoxifen is equivalent to therapeutic serum concentrations found in breast cancer patients.…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%